EDUCATION IN HUMAN RIGHTS AND MORAL DEVELOPMENT IN TEACHER FORMATION: THE INFLUENCE OF RELIGIOUSITY IN TIMES OF GENDER IDEOLOGY - Ferreira da Silva, Matheus Estevao [UNESP]; Antonelli Marcelino Brabo, Tania Suely [UNESP]; Morais, Alessandra de [UNESP] (Unesp-faculdade Ciencias & Letras, 2017)
This article, resulted of an interdisciplinary research entitled, funded by the Foundation for Research Support of the State of Sao Paulo (FAPESP) has an objective, in relation to teacher formation, the counterpoints presented to the proposal of (re) education in values of the human rights education, specifically to the themes of gender and sexuality, amid the contemporary political conjuncture. Developed from a bibliographical review and documentary analysis, the text is divided into three parts: firstly, is discussed the affirmation of the human rights education in the brazilian educational system, addressing its historical trajectory with the articulations for the formation of professionals for exercise it. Then, briefly recalling the achievements of the Feminist and LGBT movements for formal and full recognition of their rights, is highlighted the impasses for the consolidation of the human rights education that contemplate gender and sexuality, given the creation of the gender ideology on the reactionary moviment that the public policies have suffered in recent years. Finally, appropriating the cognitive theory of moral development, it is proposed a reflection on the influence of religiosity when it is dogmatically and literally processed, among the various cultural aspects, in the Brazilian moral formation, which is evidenced as one of the responsible factors by the counterpoints to the human rights education and, thus, reflecting the political scenario of indifference to historical struggles, the process of empowering subjects of rights and interfering in the laic and democratic nature of the country.
Keywords: Education; Human rights; Moral development; Gender; Sexualities; Teacher formation